A comparison of wild bee communities in sown flower strips and semi‐natural habitats: A pollination network approach. Issue 3 (10th January 2022) - Hadrava, Jiří; Talašová, Anna; Straka, Jakub; Benda, Daniel; Kazda, Jan; Klečka, Jan
Abstract: Drastic reductions of insect diversity and abundance have been observed in highly fragmented agricultural landscapes of central Europe. Declines of pollinators may have detrimental effects on the reproduction of wild insect‐pollinated plants as well as the yield of crops. In order to mitigate such impacts, sown flower strips on arable land within Agri‐Environment Climate Schemes (AECS) are supported across EU countries. However, it is not clear whether sown flower strips provide equivalent benefits to wild flower‐visiting insects as semi‐natural habitats. Here, we apply plant–pollinator network approach to evaluate the function of sown flower strips for the communities of wild bees. We compared the structural characteristics and the robustness of plant–pollinator networks in sown flower strips and nearby semi‐natural habitats in seven sites in the Czech Republic. We also quantified the importance of individual plant species for bees based on simulations of plant–pollinator extinction cascades. We found that assemblages of plants and pollinators were less diverse in sown flower strips than in semi‐natural habitats, more generalised, and more nested. However, we did not find any significant differences in network robustness to plant–pollinator coextinctions. Further, simulations revealed large variation in the functional importance among plant species from both habitats. We conclude that although the analysis of network robustness suggested that plants in the sown flower strips and semi‐natural habitats were functionally equivalent, this masked important differences between the two habitats. From a conservation point of view, semi‐natural habitats were superior in supporting a more diverse community of solitary bees and bumblebees, likely because of their greater longevity and higher habitat heterogeneity. Abstract : A comparison of sown flower strips (right) and semi‐natural habitats (left).